Emergence of compositionally tunable nanoscale dynamical heterogeneity in model binary lipid biomembranes. Issue 26 (12th June 2017) - C., Roobala; Basu, Jaydeep K.
Abstract : We have investigated dynamical heterogeneity in a two component supported lipid bilayer detected using STED–FCS and FCS diffusion law. Abstract : While the existence of nanoscale dynamical heterogeneity in biological membranes has been suggested to act as an active functional platform for enabling various cellular processes like signal transduction and viral or bacterial entry, it has been extremely difficult to detect the existence of such domains. Model lipid bilayer membranes have been widely used to detect such dynamical heterogeneity in order to avoid complications arising from the compositional heterogeneity of cellular membranes. However, even in model biological membranes the issue of nanoscale lipid dynamics has remained controversial and unresolved due to the difficulty of detecting the existence of such dynamical heterogeneity on the scale of 10–300 nm. Here we report direct evidence of nanoscale lipid dynamical heterogeneity in model binary lipid bilayer membranes using a combination of super-resolution stimulated emission depletion (STED) microscopy and fluorescence correlation spectroscopy (FCS). We control the phase behavior of the lipid bilayers by varying their composition and discuss how this leads to the emergence of dynamical lipid domains on the scale of 80–150 nm, which is also dependent on the lipid phase in which such dynamics are observed. Notably, our work shows that the presence of cholesterol is not required for the existence of such domains even in fluid like bilayers, as has been widely believed, and specifies the minimal conditions required for the emergence of such dynamical heterogeneity in cellular membranes. Our work will thus not only be of great significance towards understanding the nanoscale dynamic organizing principles of cellular membranes but could also be useful in understanding the dynamics of related soft matter systems and nanoparticle–cell membrane interactions.